2017
DOI: 10.1589/jpts.29.1844
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the vibration form roller exercise on the pains in the muscles around the hip joint and the joint performance

Abstract: [Purpose] The purpose of this study is to examine the influence of the vibration form-roller exercise on the pain in the hip joint and the joint performances. [Subjects and Methods] 30 adult patients were randomly sampled and divided into form-roller group (15) and the vibration form-roller group (15). The two groups were exposed to an exercise regimen of 3 sessions per week, over 4 weeks. Each session was composed of warming-up (5M), main exercises (20M), and five minutes of cool-down (5M). [Results] The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…However, little is known about the effectiveness of the combination of foam roller with vibration on recovery (Cheatham, Stull & Kolber, 2017; García-Gutiérrez et al, 2018; Romero-Moraleda et al, 2019). Some authors have reported greater improvements when considering knee and hip range of movement (Cheatham, Stull & Kolber, 2017; Han, Lee & Lee, 2017), indicating a reduction in muscle tightness. In addition, Cheatham, Stull & Kolber (2017), Han, Lee & Lee (2017) and Romero-Moraleda et al (2019) all reported lower perceived pain when using vibration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, little is known about the effectiveness of the combination of foam roller with vibration on recovery (Cheatham, Stull & Kolber, 2017; García-Gutiérrez et al, 2018; Romero-Moraleda et al, 2019). Some authors have reported greater improvements when considering knee and hip range of movement (Cheatham, Stull & Kolber, 2017; Han, Lee & Lee, 2017), indicating a reduction in muscle tightness. In addition, Cheatham, Stull & Kolber (2017), Han, Lee & Lee (2017) and Romero-Moraleda et al (2019) all reported lower perceived pain when using vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported greater improvements when considering knee and hip range of movement (Cheatham, Stull & Kolber, 2017; Han, Lee & Lee, 2017), indicating a reduction in muscle tightness. In addition, Cheatham, Stull & Kolber (2017), Han, Lee & Lee (2017) and Romero-Moraleda et al (2019) all reported lower perceived pain when using vibration. However, García-Gutiérrez et al (2018) and Romero-Moraleda et al (2019) showed that foam roller treatment (FR) produced increases in knee and ankle ROM with respect to a control group regardless of the use of vibration.…”
Section: Introductionmentioning
confidence: 99%
“…Foam roller may be more useful for increasing flexibility without reducing the muscle strength ratio identified by the EMG activity of the hamstring and quadriceps, as compared with other stretches (Madoni et al, 2018). Application of both normal foam roller and VFRs to patients with hip joint pain revealed improved range of motion and reduced pain (Han et al, 2017). Another study that applied a foam roller for different durations reported that the application of a foam roller for 60 sec to the quadriceps showed greater benefit than 20-sec application (Cavanaugh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that foam roller had a significantly greater effect on increasing the sit and reach distance. Han et al (2017) suggested that foam roller helped to increase the range of motion by increasing the extension and flexion of the hip joint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation